Mechatronics for Cultural Heritage and Civil Engineering (Intelligent Systems, Control and Automation: Science and Engineering,, 2018)
This book presents recent advances in mechatronic and integrated monitoring and management systems with applications to architectural, archaeology survey, construction management and civil engineering. It consists of 16 chapters authored by recognized experts in a variety of fields including dynamics, signal processing, inverse modeling, robotics and automation, in particular, here applied to design and construction of civil structures and architectural survey, monitoring and maintenance of cultural heritage assets, structures and infrastructure. The book is organized in three main sections: "Robotics and Automation", "Digital Technologies for Cultural Heritage" and "Civil Structural Health Monitoring". Topics include image processing for automated visual inspection, fiber optical sensor technology, wireless sensor monitoring, bridge inspection and monitoring of tunnel infrastructures, design tools for construction engineering, smart cities. Direct and inverse modeling of multibody systems and robots contributes to the development of applications for civil engineering and smart cities. Digital technology and mechatronic systems changes the way of looking at restoration of historical and archeological sites, analysis, inspection, visualization, management systems and sensor network for Human-Machine Interfaces (HMI). Combined use of geographical information system (GIS), laser scanner, remote sensing, digital thermography and drones as integrated systems permits to highlight new frontier for building and infrastructure knowledge. The book offers a valuable reference work for scientists, architects, engineers, researchers and practitioners in engineering and architecture since the integrated development of new technologies for the design and management of existing and new infrastructure may produce a new market of services and products for safe and economically optimized infrastructure management. Through the dissemination of advanced research developments in mechatronics and integrated management systems, the book promotes exchanges and collaborations among researchers of different disciplines. The book contributes to further advancements in the rapidly growing field of integration of robotic, automation and information technologies in the area of facilities and infrastructure management and construction processes.